The Visual Narrative of Satria Barong's Character as a Representation of the Mystical Entity of Barong Ket - Agus Suarya Putra, Nyoman; Marthana Yusa, Made; Yudi Arsana, Gede (KnE Social Sciences, 2023)
This study aims to bring the aesthetic, ethical and cultural values contained in the Barong Bali entity to the audience through a modern cultural paradigm. The physical form of Barong—specifically the chosen one – is Barong Ket. Modified with a popular culture approach, specifically selected, is the Japanese Pop culture approach in terms of the concept and terminology of Tokusatsu. The modification of Barong’s form is carried out with an art creation model that involves exploratory and experimental aspects. This exploratory and experimental activity, as an initial methodological step, was carried out to find the ideal visual structure as a result of modifying the Barong Ket entity form to the Tokusastsu Barong model. Next, a narrative strategy is designed with a visual narrative approach. Reference studies were conducted to find supporting literature and audio-visual references. The supporting literature in question is related to transformative art, modification of visual forms, visual narratives, and Japanese pop culture models, especially the tokusatsu genre. The next methodological step in the creation of this art is to realize a visual narrative strategy in the form of presenting a short film performance. This process involved designing and creating art resulted in a short film with a special message delivered to each scene. Before being officially broadcast, an initial evaluation was carried out involving videographers, filmmakers and art observers as evaluators. This evaluation was carried out using a structured interview technique with the aim of exploring the research aspects to be evaluated more broadly and in depth. From the evaluation results, the short film entitled Satria Barong was feasible to be shown to the target audience with a note that there was an emphasis on detailed visual introductions. Keywords: visual narrative, Satria Barong, Tokusatsu